Electronic band dispersion of graphene nanoribbons via Fourier-transformed scanning tunneling spectroscopy - Soede, Hajo; Talirz, Leopold; Groning, Oliver; Pignedoli, Carlo Antonio; Berger, Reinhard; Feng, Xinliang; Muellen, Klaus; Fasel, Roman; Ruffieux, Pascal (Physical Review B - Condensed Matter and Materials Physics, 2015)
The electronic structure of atomically precise armchair graphene nanoribbons of width N=7 (7-AGNRs) are investigated by scanning tunneling spectroscopy (STS) on Au(111). We record the standing waves in the local density of states of finite ribbons as a function of sample bias and extract the dispersion relation of frontier electronic states by Fourier transformation. The wave-vector-dependent contributions from these states agree with density functional theory calculations, thus enabling the unambiguous assignment of the states to the valence band, the conduction band, and the next empty band with effective masses of 0.41±0.08me,0.40±0.18me, and 0.20±0.03me, respectively. By comparing the extracted dispersion relation for the conduction band to corresponding height-dependent tunneling spectra, we find that the conduction band edge can be resolved only at small tip-sample separations and has not been observed before. As a result, we report a band gap of 2.37±0.06 eV for 7-AGNRs adsorbed on Au(111).
CRIS-Team Scopus Importer:2023-03-20